Zad. 1
a)
[tex]2t + 4 = t - 3 \ \ \ |-4 \\ 2t = t - 7[/tex]
b)
[tex]1 - 3t = 3 - 4t \ \ \ |+4t \\ 1 + t = 3[/tex]
c)
[tex]x = \frac{1}{5} x- 3 \ \ \ |- \frac{1}{5}x \\ \frac{4}{5}x = - 3[/tex]
d)
[tex]\frac{1}{4} y = 3 + y \ \ \ |-y \\ - \frac{3}{4}y = 3[/tex]
e)
[tex]\frac{x+1}{4} =\frac{2x+1}{2} \ \ \ |\cdot 4 \\ x + 1 = 4x + 2[/tex]
f)
[tex]3(x - 8) = 6x - 9 \ \ \ |:3 \\ x - 8 = 2x - 3[/tex]
g)
[tex]x - \frac{1}{3}x = \frac{1}{6} - 2x \ \ \ |\cdot 6 \\ 6x - 2x=1 - 12x[/tex]
h)
[tex]1 - x = \frac{2x-3}{5} \ \ \ |\cdot 5 \\ 5 - 5x = 2x - 3[/tex]